CORRELATION OF FREE LARVAE INDEX AND POPULATION DENSITY WITH DENGUE FEVER INCIDENCE RATE - Ria Nuranisa; Yusuf Budi Maryanto; Muhammad Atoillah Isfandiari (Universitas Airlangga, 2022)
Introduction: Dengue Hemorrhagic Fever (DHF) is a disease caused by the dengue virus that infects the body. Dengue is a common viral infection in warm tropical climates. The infection is caused by one of four closely related dengue viruses. The disease now plagues many countries and even more than 100 countries within the WHO, including Africa, the Americas, the Eastern Mediterranean, Southeast Asia, and the Western Pacific. The Americas, Southeast Asia, and the Western Pacific are the most severely affected regions, with Asia representing 70% of the global disease burden. The high incidence rate of DHF in various regions of Indonesia is the background by several factors, one of which is the density of the seaters. The aim of this study was to analyze the correlation between population density and larvae free index and Incidence Rate (IR) Dengue Hemorrhagic Fever (DHF) in Blitar Regency in 2013-2017. Methods: The data were analyzed quantitatively using Spearman correlation tests to analyze relationships between variables. Result: The results of the analysis found there was no correlation between dengue fever incidence rate and larvae free index (p = 0.603 r = -0.117), and there was a correlation between the incidence rate of dengue fever and population density (p = 0.002 r = 0.619). Conclusion: High population density is a risk factor for DHF events in Blitar Regency, so there needs to be an anticipation of preventive measures such as the implementation of 3M and counseling of the impact of high population density.